2014
DOI: 10.2478/s11535-014-0301-6
|View full text |Cite
|
Sign up to set email alerts
|

The action of CGRP and SP on cultured skin fibroblasts

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
(106 reference statements)
0
2
1
Order By: Relevance
“…For the concentrations of 1 × 10 −8 , 1 × 10 −7 and 1 × 10 −6 M, the free and encapsulated SP stimulated cell proliferation in a manner not significantly different (within 15%) than in the untreated controls. This finding conflicts with earlier studies, which observed that SP can promote proliferation of spinal cord-derived neural stem cells [ 59 ], bone marrow stromal cells, [ 15 ] and fibroblasts [ 18 ]. Further, a previous study showed that SP stimulated cellular proliferation of keratinocytes in vitro in a concentration-dependent manner when SP was added in the concentration range of 1 × 10 −10 to 1 × 10 −7 M [ 11 ].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…For the concentrations of 1 × 10 −8 , 1 × 10 −7 and 1 × 10 −6 M, the free and encapsulated SP stimulated cell proliferation in a manner not significantly different (within 15%) than in the untreated controls. This finding conflicts with earlier studies, which observed that SP can promote proliferation of spinal cord-derived neural stem cells [ 59 ], bone marrow stromal cells, [ 15 ] and fibroblasts [ 18 ]. Further, a previous study showed that SP stimulated cellular proliferation of keratinocytes in vitro in a concentration-dependent manner when SP was added in the concentration range of 1 × 10 −10 to 1 × 10 −7 M [ 11 ].…”
Section: Resultscontrasting
confidence: 99%
“…In the skin, SP has been related to the neurogenic inflammation, as it stimulates the regeneration of wounds via inducing the release of nerve growth factors [ 17 ], intensifying the migration of keratinocytes [ 14 ] and stimulating the proliferation of fibroblasts [ 18 , 19 ]. Improving our understanding on the action of SP and its effects on skin wound healing could be of relevance, for example, in the treatment of diabetic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…An important caveat, however, is that the anti-inflammatory function of SP cannot be universally ascribed to every cell type as this neuropeptide appears to have a pro-inflammatory effect in keratinocytes. 77 It is interesting to note that other neuropeptides such as calcitonin gene related peptide [78][79][80] may also be considered as an anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%